A FINITE ELEMENT ANALYSIS: THE EFFECT OF CORROSION ON THE SEISMIC PERFORMANCE OF A FIBER REINFORCED CONCRETE COLUMN - Rizaldi, Niko
Reinforced concrete structures exposed to the marine environment have a high risk of corrosion. The influence of corrosion will degrade the performance of the structure through the degradation of the strength of the reinforcing steel, the weakening of the adhesions between steel and concrete, and the cracking of concrete caused by corrosion products. Another threat will be experienced by the structure if it is in the earthquake area because it is vulnerable to receiving corrosion effects and seismic loads at once. Some researchers have tried to develop breakthroughs that can mitigate the impact of reinforced concrete damage caused by corrosion. One such innovation is fibrous reinforced concrete (FRC). This thesis aims to examine the effect of corrosion on the seismic performance of elements of reinforced concrete column structures with fibers. The research method used is finite element analysis, which is developed from the experimental results that have been carried out. There are three approaches proposed in element analysis with the aim of validating experimental results, including modeling the behavior of concrete materials in tensile and compressive conditions, the behavior of reinforcing steel, and the influence of bond-slips between reinforcement and concrete. The specimens used are column elements with the influence of corrosion along the plastic joints, while the load application is applied laterally cyclically with a displacement control system. The results of validation between experimental and finite element analysis become a reference for the development of specimens with variations in fiber addition and different levels of corrosion. The fiber parameters used in specimens are 0%, 0.5%, 1%, and 2%, with corrosion levels of 0%, 5%, 10%, 30%, and 50%. Based on the results of finite element analysis, it was found that the addition of fiber is good to use at the medium corrosion level (about < 20%). This is evidenced by an increase in strength of about 6.6% against structures that have been corroded without fibers. In addition, the ductility and dissipation energy of fibrous reinforced concrete columns also increased by about 16.23% and 31.04% compared to fiberless reinforced concrete columns. While at the level of severe corrosion (about > 20%) Additional fibers are not optimally used because reinforced concrete structures have shown brittle behavior.